Dynamic movement of the Golgi unit and its glycosylation enzyme zones - Akihiro Harada; Masataka Kunii; Kazuo Kurokawa; Takuya Sumi; Satoshi Kanda; Yu Zhang; Satomi Nadanaka; Koichiro M. Hirosawa; Kazuaki Tokunaga; Takuro Tojima; Manabu Taniguchi; Kenta Moriwaki; et al. (Nature Communications, 2024)
Abstract Knowledge on the distribution and dynamics of glycosylation enzymes in the Golgi is essential for better understanding this modification. Here, using a combination of CRISPR/Cas9 knockin technology and super-resolution microscopy, we show that the Golgi complex is assembled by a number of small ‘Golgi units’ that have 1-3 μm in diameter. Each Golgi unit contains small domains of glycosylation enzymes which we call ‘zones’. The zones of N- and O-glycosylation enzymes are colocalised. However, they are less colocalised with the zones of a glycosaminoglycan synthesizing enzyme. Golgi units change shapes dynamically and the zones of glycosylation enzymes rapidly move near the rim of the unit. Photobleaching analysis indicates that a glycosaminoglycan synthesizing enzyme moves between units. Depletion of giantin dissociates units and prevents the movement of glycosaminoglycan synthesizing enzymes, which leads to insufficient glycosaminoglycan synthesis. Thus, we show the structure-function relationship of the Golgi and its implications in human pathogenesis.